Occupational therapy upper limb splinting practice for clients with acquired brain injuries : a cross-sectional study from South Africa - van Wyk, Megan Barbara (Stellenbosch : Stellenbosch University, 2022)
Thesis (MOccTher)--Stellenbosch University, 2022.